Dilsel Çeşitliliğin Sınırları: Türkçenin Azrak Dil Özellikleri - Çağrı AKKUŞ; Özge CAN (Dilbilim Araştırmaları Dergisi)
The effort to understand the universal features of language often brings linguistic typology studies, which develop by identifying common structural features among languages, to the forefront. These studies focus on the general features of languages while features that fall outside of generalizations, in other words, those that are less frequently seen in languages, are labeled as exceptions to generalizations. However, features that are considered exceptions to the generalizations have a vital role in revealing the limits of linguistic variety. In this study, the features that are exceptions to the generalizations, categorized by the the terms rara, rarissima, infrequent and unique, are gathered under the title of ‘rare linguistic features’. World Atlas of Language Structures online database was used to determine the rare language features Turkish has compared to the world languages and to categorize the resulting features based on Cysouw’s (2011) threshold of ≤7.2%. According to the data obtained, three rare infrequent features were determined in Turkish: the simultaneous presence of high front rounded vowel /y/ and middle front rounded /ø/ phonemes in the inventory (%4), evidentiality being a part of the tense system (%5.7) and having no definite article but indefinite article.